2001
DOI: 10.1139/v01-007
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting oxygen delignification of kraft pulp

Abstract: Softwood kraft pulp was subjected to a laboratory one- and three-stage oxygen delignification process. Pulp and liquor samples were collected at different stages of the process with particular attention being paid to the early and late stages. A novel residual lignin isolation method extracted about 65% of the oxidized residual lignins at a purity exceeding 90%. Using this methodology coupled to quantitative 31P NMR, 13C NMR, 2D heteronuclear (HMQC) NMR spectroscopic and analytical pyrolysis techniques allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
4
39
1
1
Order By: Relevance
“…The significant observation from the reported results is that the S-type compounds increase with an increase in the severity of the wet explosion conditions. This was found to contradict the previous observations made by studying the effect of steam explosion and wet oxidation separately on lignocellulosic biomass [30][31][32][33][34] since these studies indicated that S units after pretreatment are cleaved to produce more G units resulting in a reduction in the S/G ratio and an increase in the lignin surface condensation. However, from both the NMR and the GC-MS analysis, wet explosion pretreatment showed an increase in the S units and decrease of H and G, which could best be explained through a selective methoxylation of H and G lignins during the pretreatment.…”
Section: Lignin-derived Phenolic Compounds As Determined By Gc/mscontrasting
confidence: 67%
See 1 more Smart Citation
“…The significant observation from the reported results is that the S-type compounds increase with an increase in the severity of the wet explosion conditions. This was found to contradict the previous observations made by studying the effect of steam explosion and wet oxidation separately on lignocellulosic biomass [30][31][32][33][34] since these studies indicated that S units after pretreatment are cleaved to produce more G units resulting in a reduction in the S/G ratio and an increase in the lignin surface condensation. However, from both the NMR and the GC-MS analysis, wet explosion pretreatment showed an increase in the S units and decrease of H and G, which could best be explained through a selective methoxylation of H and G lignins during the pretreatment.…”
Section: Lignin-derived Phenolic Compounds As Determined By Gc/mscontrasting
confidence: 67%
“…The implication of this study is significant since it is generally accepted that the action of oxygen on softwood lignin usually enriched its H units [33]. These studies have attributed this increase in H units with its high recalcitrance during oxygen delignification.…”
Section: Two-dimensional Hsqc Nuclear Magnetic Resonancementioning
confidence: 67%
“…This compound interferes in protein estimation based on N content (1-2% N can be found in most residual lignins, but up to 5% N after laccase mediator treatment). The enrichment in lignin H units during pulp delignification reported in other studies (Akim et al 2001;Tamminen et al 2003) is most probably due to contaminating protein, as tyrosine residues gives rise to the same Py-GC/MS products and HSQC correlations (Choi and Faix 1998).…”
Section: Tablementioning
confidence: 74%
“…Under alkaline conditions, oxygen is an efficient oxidizing agent for organic compounds, resulting in the formation of various reactive oxygen intermediates, such as hydroperoxyl and hydroxyl radicals, hydrogen peroxide, and hydroperoxide anions. The complicated oxidation process of oxygen delignification involves several radical chain reactions, which are combined with various organic compounds mainly originating from lignin, carbohydrates, and some extractives (Starnes Jr. 1980;McDonough 1996;Alén 2000;Akim et al 2001;Kalliola et al 2011). From lignin, oxidative degradation leads to the formation of various aliphatic carboxylic acids via different intermediates, such as catechol, quinone, and muconic acids Rovio et al 2011).…”
Section: Oxygen-alkali Delignificationmentioning
confidence: 99%